Comparative detection of salmonella in Philippine desiccated coconut using loop-medicated isothermal amplification (LAMP), dry film plating, and selective medium plating - Tongco, Anna Margarita P.; Gabriel, Alonzo Alulod (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This study was conducted to compare three detection methods for Salmonella in Philippine desiccated coconut, namely, loop-mediated isothermal amplification (LAMP) assay, dry film plating method, and selective culture medium used in conventional culture method. Desiccated coconut was decontaminated by heat under pressure and spray-inoculated with the test cultures prior to method testing. The study showed that all three methods were inclusive and exclusive for Salmonella detection, and detection was not hampered by the presence of non-Salmonella microorganisms. The study also established ultraviolet-C-mediated inactivation of Salmonella in desiccated coconut at 3 log cycles after 40 min exposure to radiation. The radiation treatment did not affect the color acceptability of the samples. The study concluded that, while LAMP was the most sensitive and had the fastest time to result, the other two methods were also competent, in terms of sensitivity, selectivity, and inclusivity-exclusivity, in detecting Salmonella in desiccated coconut. It also concluded that UV-C radiation may be considered for post-processing of desiccated coconut, particularly against Salmonella spp.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Coconut -- Philippines